Exploring the role of strategic environmental assessment in cultural heritage tourism planning: a case study of the Srirangapatna-Mysore region in India. Issue 2 (4th March 2021) - Jha-Thakur, Urmila; Khosravi, Fatemeh; Quattrone, Giamila; Bandyopadhyay, Soumyen; Magedera, Ian; Garikipati, Supriya
ABSTRACT: Sustainability is critical to the delivery of cultural heritage tourism (CHT) since its foundation to attract tourist relies on the preservation of the historic and cultural offerings of the host community. CHT destinations within urban and semi-urban heritage sites in emerging economies find this particularly challenging. To explore this issue and its associated challenges, this paper brings together an interdisciplinary team representing disciplines of heritage management, architectural and cultural history, economics, environmental planning and sustainability to establish the extent to which sustainability principles are integrated within CHT destinations in the semi-urban destinations of emerging economies. An interdisciplinary analysis of the case study of Srirangapatna-Mysore region in India, using a framework for evaluating sustainability principles within CHT reveals environmental considerations to be the weakest link. Accordingly, Strategic Environmental Assessment (SEA) is proposed as a tool that can compensate some of the caveats identified in the case study by potentially enhancing stakeholder involvement, raising heritage and environmental awareness, facilitating regional approach and avoiding costly mistakes.